MERANCANG INOVASI MODEL PELATIHAN FOOD AND BEVERAGE SERVICE BERBASIS KOMPETENSI DI LEMBAGA PELATIHAN KERJA (STUDI KASUS DI LPK DENPASAR) - Ida Bagus Nyoman Weda; I Made Darsana; Agus Made Yoga Iswara (CV. Lafadz Jaya, 2026)
The tourism industry plays a strategic role in the economic development of Bali, particularly through the accommodation and food and beverage sectors, which contribute significantly to the region’s Gross Regional Domestic Product. The growth of the hospitality sector requires the availability of a workforce with professional competencies that align with industry standards. However, previous studies indicate a competency gap between graduates of vocational training institutions and the actual needs of the hospitality industry, particularly in the field of Food and Beverage Service (FBS). This study aims to analyze the existing FBS training model implemented in Job Training Institutions (Lembaga Pelatihan Kerja/LPK) in Denpasar, identify competency gaps between training outcomes and industry requirements, and develop an innovative competency-based training model that is more responsive to the dynamics of the hospitality industry. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, participant observation, Focus Group Discussions, and document analysis involving training institution managers, instructors, trainees, and representatives from the hospitality industry. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings reveal that the FBS training model implemented in LPK Denpasar has adopted the principles of competency-based training with a dominant proportion of practical learning and a curriculum referring to the Indonesian National Work Competency Standards (SKKNI). Nevertheless, the training model remains primarily oriented toward meeting basic competency standards and has not been fully integrated with the dynamic operational demands of the hospitality industry. The study also identifies competency gaps in both technical and soft skills that affect graduates’ job readiness. In response to these findings, this research proposes a Best Practice CBT Model that integrates the Competency-Based Training approach, the ADDIE instructional design framework, and the link-and-match principle with industry. The proposed model is expected to enhance graduates’ job readiness and strengthen the effectiveness of vocational training in the hospitality sector.